Penerapan Breathing Exercise Terhadap Sesak pada Pasien Pneumonia: Literatur Review - Hanif Rineldi Ramadan; Putri Irwanti Sari (MES Bogor, 2025)
Pneumonia is an inflammatory condition of the respiratory tract and lung tissue caused by viruses, bacteria, or fungi. It is the leading cause of death in children under five, with estimates that every 20 seconds, a child under five dies from pneumonia. Despite being a significant cause of death, pneumonia is often overlooked due to low detection, non-specific symptoms, and lack of attention in treating this problem. The management of pneumonia does not only focus on the administration of antibiotics, but also involves supportive therapies such as respiratory physiotherapy. Breathing exercises are one of the simple interventions that have been proven effective in helping relieve complaints of shortness of breath in pneumonia patients. This article aims to review the literature related to the application of breathing exercises in overcoming shortness of breath in pneumonia patients as a basis for developing clinical interventions. The method used is SLR (Systematic Literature Review) by analyzing, reviewing and drawing conclusions that are relevant to the research topic and can be accounted for. The results of the analysis of several articles showed that the application of breathing exercise in shortness of breath pneumonia is effective in the long term and easy to apply directly by everyone. In this case it is concluded that Breathing exercise is scientifically proven to be able to reduce the level of shortness of breath, increase oxygen saturation, and slow down breathing.